The Origin of The Legendary Specialty Food Nasi Uduk: A Review of SWOT Analysis - Pradini, Gagih; Awaloedin, Dipa Teruna; Agustiani, Fitri; Izati , Citra Nur Sabrina; Saroso, Adiyasa; Anjani, Rheka Dwi (CV ODIS, 2024)
Tourism is an activity that involves the travel and visit of a person or group of people to a place or area outside of their place of residence for recreational, leisure, business, or educational purposes. The term tourism encompasses various activities such as travel, lodging, food, and other recreational activities undertaken by tourists during the period of their visit. Culinary tourism is a travel activity or part of it that is carried out voluntarily and temporarily to enjoy typical food or drinks. One of the culinary in Jakarta, namely Nasi Uduk is white rice cooked with coconut milk sauce so that the rice is slightly